Implementation of Active Learning in Improving Student's Exposition Writing Ability - Karim, Hajir Maimuri; Marcela, Eny Dwi (Master Program in Indonesian Language Education and The Institute for Research and Community Service STKIP PGRI Bandar Lampung, 2020)
This study aims to determine the implementation of active learning in improving the ability to write exposition students of class VIII MTs Negeri 2 Bandar Lampung, so this research can be used as a reference for one of the learning methods that can be used to improve learning achievement. The method used to achieve this goal, the researcher uses a data collection method where the methods used by researchers to collect data are observing the variables to be studied using interviews, tests, observations, and questionnaires. The results of the study can be concluded that using the jigsaw cooperative learning method can improve learning achievement in Indonesian material about exposition texts in class VIII students of MTs Negeri 2 Bandar Lampung in the 2019/2020 academic year. This can be proven from the pre-cycle of students who completed as many as 12 students with a percentage of completeness of 37.5%. The first cycle of students who completed increased to 20 students with a percentage of completeness of 62.5%. The target of classical completeness criteria is with a percentage of 85% achieved in cycle II with a completeness percentage of 100% with 32 students who complete. Pre-cycle to cycle I an increase of 25%, while the first cycle to cycle II an increase of 37.5%. This Classroom Action Research was declared successful.